Theoretical Basis Of The Concept Of Individual Approach And Its Role In The Educational Process - Yangibayev Kamol Norboyevich (Genius Journals, 2025)
This article discusses the theoretical foundations of the concept of an individual approach and its role in the educational process. It also provides practical recommendations for increasing the effectiveness of this approach and analyzes aimed at better understanding its role in education
Keywords: Individual approach; education; pedagogical foundations